Effects of Moringa oleifera LAM, Leguminous Plants and NPK Fertilizer Comparatively on Orange Fleshed Sweet Potato in Alley Cropping System - Abdullahi, IN; Anyaegbu, PO; Aliagbor, D (International Journal of Environment, 2014)
The research work conducted at the Teaching and Research Farm of University of Abuja was aimed at assessing the effect of Moringa oleifera, selected leguminous plants and inorganic fertilizer on the performance of orange fleshed sweet potato in Alley Cropping System. Randomized Complete Block Design (RCBD) using five treatments with three replications was applied. Data collected include: percentage survival of sweet potato, length per vine (cm), number of leaves per vine, leaf area of sweet potato, weed dry matter (g/m2), yield of sweet potato roots. Highest number of leaves (28) per plant was recorded in the control plot while the plots with NPK fertilizer had the highest length per vine (94.55cm) though not significantly (p>0.05) different from others. Higher percent survival (88%) of sweet potato was recorded from control plots. Stands grown in Arachis hypogeae plots produced the highest leaf area (0.202m2) while plots in which NPK fertilizer was applied experienced highest weed dry matter (4.083g/m2) although highest root yield (1.2t/ha) was recorded from the plots with NPK fertilizer. DOI: http://dx.doi.org/10.3126/ije.v3i3.11061 International Journal of Environment Vol.3(3) 2014: 24-35